1991
DOI: 10.1128/aem.57.5.1313-1318.1991
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of oligonucleotide probes for identification of Lactococcus lactis subsp. cremoris

Abstract: Lactococcus lactis subsp. cremoris is of considerable interest to the dairy industry, which relies upon the few available strains for the manufacture of cheddar cheese free of fermented and fruity flavors. The subspecies cremoris differs from related subspecies by the lack of a few phenotypic traits. Our purpose was to identify unique rRNA sequences that could be used to discriminate L. lactis subsp. cremoris from related subspecies. The 16S rRNAs from 13 Lactococcus strains were partially sequenced by using r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(86 citation statements)
references
References 25 publications
3
83
0
Order By: Relevance
“…lactis (Chiaruttini and Milet 1993) or subsp. cremoris (Salama et al 1991) was observed in the sequences of strains G50, H45, H59 and…”
Section: Identification Of the Isolatesmentioning
confidence: 95%
“…lactis (Chiaruttini and Milet 1993) or subsp. cremoris (Salama et al 1991) was observed in the sequences of strains G50, H45, H59 and…”
Section: Identification Of the Isolatesmentioning
confidence: 95%
“…lactis subsp. cremoris and vice versa (Salama et al 1991(Salama et al , 1993Godon et al 1992;Klijn et al 1995). In a recent study, three molecular typing methods [partial SSU (small subunit) rRNA gene sequence analysis, (GTG) 5 -PCR genomic fingerprinting analysis and multilocus sequence analysis (MLSA) scheme] applied to a collection of lactococcal strains from various dairy and plant fermentations and a wide range of geographic locations revealed two major distinct genomic lineages within the species that are dissimilar to groups defined on the basis of phenotypic analysis (Rademaker et al 2007).…”
Section: Lactococcus Lactismentioning
confidence: 99%
“…4). Originally, both strains were classified in the subspecies lactis on phenotypic criteria but analysis of DNA-DNA reassociation [5], and 16S RNA sequences [104,105], direct gene sequence comparisons and Southern hybridization analysis with cloned chromosomal genes as probes [106] indicated that MG1363 and the closely related strains NCDO712, NCDO763 (ML3), NCDO505 (C2), LM2301 belong genotypically to the subspecies cremoris. The high degree of restriction polymorphism between IL1403 and MG1363 is consistent with the divergence of genomic sequences between L. lactis subsp, lactis…”
Section: Comparison Of the Genomic Mapsmentioning
confidence: 99%